Meningkatkan Hasil Belajar Dengan Menggunakan Model Pembelajaran Kooperatif Berbantuan Media Diorama Pada Mata Pelajaran IPA di Kelas V SD Negeri 066656 T.A 2023/2024 - Magdalena, Rupina; Sitepu, Try Bion (JURNAL CURERE, 2024)
This research aims to determine the improvement in learning outcomes by using a cooperative learning model assisted by diorama media in science subjects in class V of SD Negeri 066656 for the 2023/2024 academic year. The research carried out was classroom action research, the subjects of this research were class V students at SD Negeri 066656, totaling 27 students. The object of this research is the use of a cooperative model assisted by diorama media in science subjects in class V of SD Negeri 066656. To determine the implementation of student learning, the data collection tools used in this research are observation sheets and description tests. Before conducting research and treatment, researchers carried out a pre-cycle and obtained an average result of 52.41. Next, the researcher carried out the treatment using a cooperative learning model assisted by diorama media. In cycle I, the average was 62.59 and in cycle II, the average was 88.52. The results of this research showed that in the pre-cycle it was 29.63%, increasing in the first cycle with 12 students who not completed (44.45%) and 15 students who did complete (55.55%). Furthermore, in cycle II, there were 25 students who completed (92.59%) and 2 students who did not complete (7.40%). Based on the results of the research carried out, it can be concluded that implementing learning using a cooperative model assisted by diorama media in science subjects in class V of SD Negeri 066656 for the 2023/2024 academic year can improve student learning outcomes